0516 Positive Airway Pressure Compliance In Post-acute Stroke And Traumatic Brain Injury Patients. (12th April 2019) - Howell, Stefanie; Robinson, Stephanie; Griesbach, Grace
Abstract: Introduction: The objective was to investigate positive airway pressure (PAP) compliance following brain injury in a post-acute rehabilitative setting. Methods: Adult brain-injured patients (n=21) diagnosed with sleep apnea via overnight polysomnography were assessed for PAP compliance using compliance online databases. The mean age was 54 ± 2 years, mean latency from injury was 119 ± 15 days, and mean days on PAP treatment was 104 ± 20 days. Compliance measures included total percentage of days used since setup and % of days used ≥4 hours. We also considered average AHI while on PAP treatment, mask type, and apnea severity. Results: Overall, 43% of patients were using their PAP machines ≥70% of days since setup, and were considered compliant. Of those compliant patients, 88% were using full face masks; however, 63% of them continued to have a clinically significant AHI. Of the compliant patients, 67% had a diagnosis of severe sleep apnea, with an AHI > 30, while only 40% of the non-compliant patients were considered severe (60% of these patients were non-compliant on PAP therapy prior to their injuries). In addition to apnea severity, patients who were compliant after at least 3 months of therapy were compliant immediately after receiving their machines and had a strong family support system vs. the patients who were considered non-compliant. Conclusion: Despite being compliant with PAP therapy, patients using full face masks were still experiencing clinically significant AHI, indicating large leaks and a poor mask fit. In a brain-injured population, apnea severity seems to predict PAP compliance, as does initial compliance and having a strong support system at home. Support (If Any)